Identifying threshold concepts in postgraduate general practice training: a focus group, qualitative study - Katherine Hall; Anna Chae (BMJ Open)
Objective To identify threshold concepts (TCs) for physicians undergoing postgraduate medical education (PGME) in general practice.Design An explorative, qualitative study with 65 min focus group interviews and thematic analysis was used. Participants were asked to describe their most transformative learning experiences. Heuristical TCs were identified from the thematic analysis.Setting Aotearoa/New Zealand (A/NZ).Participants Fifty participants, mostly comprising current trainees and educators from urban centres, and of NZ/European ethnicity.Results Twenty TCs covering many aspects of postgraduate general practice experience were derived from themes identified in the data. Presented in medical proverbial form for ease of recollection, these included: Money makes the practice go round; Be a legal eagle; Manage time or it will manage you; Guidelines, GPs’ little helpers; Right tool, right word, right place; The whole of the practice is greater than the sum of the parts; The personal enhances the professional; Beat biases by reflection; Chew the Complexity, Unpredictability, Diversity; Embrace the uncertainty; Not knowing is knowing; Seek and you shall find; Waiting and seeing, waiting and being; Look, listen, think between the lines; Treat the patient beyond the disease; No patient is an island; Words work wonders; Hearing is healing; Being you and being there; and; The relationship is worth a thousand consults. These TCs mapped onto core competencies in A/NZ’s PGME in general practice curriculum.Conclusions Participants readily identified transformative and troublesome moments in their PGME in general practice. These findings confirmed evidence for a wide range of TCs with many newly identified in this study. All TCs were fundamentally based on the doctor–patient relationship, although often involving the context and culture of general practice. Actively incorporating and teaching these identified TCs in PGME in general practice may enable trainees to grasp these important learning thresholds earlier and more easily and aid in identity and role formation.